TIME-RELATED STRATEGIES IN CHESS (BLITZ, RAPID, CLASSICAL) (Modern American Journal of Social Sciences and Humanities, 2025)
Chess, as an intellectual game, requires distinct strategic approaches depending on time control formats (blitz, rapid, classical). This article provides a scientific analysis of time-related strategies, exploring the characteristics of blitz, rapid, and classical formats, as well as their psychological and physiological impacts on players. It examines time management techniques, the role of player experience, and the influence of modern technologies (computer programs, online platforms) in shaping these strategies. Additionally, practical applications of time strategies are illustrated through examples from professional players (e.g., Magnus Carlsen, Hikaru Nakamura). The article serves as a valuable resource for higher education students and chess researchers.